2005
DOI: 10.1002/anie.200500031
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Observation of Green Multiphoton Upconversion and Red and Blue NLO Processes from Polymeric Terbium(III) Complexes

Abstract: Photoexcitation at a certain wavelength in the near-infrared (NIR) region followed by luminescence at a shorter wavelength in the visible domain is called near-infrared-to-visible photon upconversion. This is a rather unusual process as lowenergy photons are "converted" into higher energy photons: two or three photons of NIR light are required to generate one photon of visible light.[1] Nonlinear optics (NLO) is another mechanism that can lead to the generation of light at a frequency that is either twice or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…480 To close this short overview of MPA phenomena in lanthanide complexes, we would like to mention the polymeric Tb III complex [Tb(NO 3 ) 3 (57c)] n , which upon laser excitation at 1.26 mm exhibits green Tb III emission from a 4PA process as well as blue and red emission resulting from single and third harmonic generation, the complex playing the role of the gain medium. 481 Two-photon excitation luminescence microscopy is a relatively new technique which started in the 1990s. 482 Besides using a ''cell-friendly'' NIR excitation wavelength, it allows the imaging of difficult samples with good resolution.…”
Section: The Advent Of Multiphoton Excitationmentioning
confidence: 99%
“…480 To close this short overview of MPA phenomena in lanthanide complexes, we would like to mention the polymeric Tb III complex [Tb(NO 3 ) 3 (57c)] n , which upon laser excitation at 1.26 mm exhibits green Tb III emission from a 4PA process as well as blue and red emission resulting from single and third harmonic generation, the complex playing the role of the gain medium. 481 Two-photon excitation luminescence microscopy is a relatively new technique which started in the 1990s. 482 Besides using a ''cell-friendly'' NIR excitation wavelength, it allows the imaging of difficult samples with good resolution.…”
Section: The Advent Of Multiphoton Excitationmentioning
confidence: 99%
“…The first series of lanthanide complexes (Type I) with La (1), Ce (2), Nd (4), Sm ( 5), Eu (6), Gd (7) and Tb (8), where the ionic radius of Ln 3+ is between 103 and 92 pm, crystallize in the trigonal system R3c (Fig. 3, Type I) and the other seven complexes (Type II) comprise Dy (9), Y (10), Ho (11), Er (12), Tm (13), Yb (14) and Lu (15), where the ionic radius of Ln 3+ is between 91 and 86 pm, and crystallize in the primitive monoclinic system P2 1 (Fig. 3, Type II).…”
Section: Solid State Structures Of Lanthanide Complexesmentioning
confidence: 99%
“…[10][11][12] We have reported a novel system for which multiphoton absorption produced second and third harmonic generation (SHG and THG) simultaneously with intraconfigurational 4f emission. 13,14 The variations in coordination geometry of the central metal atom, and also the ligation of carboxylate ions in lanthanide carboxylate complexes, are both interesting themes of structural chemistry. [15][16][17] Over the past twenty years, many structural studies of lanthanide carboxylates have been reported, where diverse coordination types have been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence processes from organic-lanthanide complexes are usually induced by an organic chromophoric ligand that absorbs light and transfers this excitation energy to the lanthanide ion [6], [13,14]. In recent years, limited numbers of organic-terbium complexes have been reported for in-vitro imaging with low two-photon quantum efficiency, for example, a Tb III -protein complex for in-vitro imaging with 20 GM at 800 nm [5], and our recently reported Tb-polymeric tripodal amide complex showing values of $2.6 GM in the spectral region of 800 nm [4].…”
Section: Resultsmentioning
confidence: 99%